The Effect of Brand Ambassador and Electronic Word of Mouth on The Purchase Decision of Erigo Apparel Products With Brand Image As An Intervening Variable - Putra, Rheznandya Aranda; Edy Purwo Saputro (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the impact of brand ambassador and electronic word of mouth (E-WOM) on the purchase decision of Erigo Apparel products, with brand image as an intervening variable. A quantitative research approach was used, where primary data was collected through questionnaires distributed to 100 students in Surakarta. The study utilized purposive sampling and employed a five-point Likert scale to measure the responses. The data was analyzed using SPSS Statistics 22, including classical assumption tests, multiple linear regression, and hypothesis testing with the F test and t test. The findings indicate that brand ambassador has a negative but insignificant effect on purchase decisions, while E-WOM has a positive and significant influence. Brand image was found to have a negative but insignificant effect. The study suggests that future research should explore additional variables and larger sample sizes for more comprehensive insights into factors affecting purchase decisions.